SIGAP Application Quality Through Webqual Analysis: Kualitas Aplikasi SIGAP Melalui Analisis Webqual - Lazim, Moch. Faex; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2023)
In this study, the SIGAP application is deemed necessary to be investigated and dissected more deeply, because in the last few years there are still many people who do not know the functions and uses of the SIGAP application as the first natural disaster response application in Sidoarjo Regency. This study uses quantitative methods and uses an approach through statistical data. This study focuses on volunteers who have downloaded the SIGAP application. Researchers set 88 people as a sample to be later developed into statistical data. By using the technique of Non Probability Sampling, data collection in this study using questionnaires and observations. This study uses descriptive statistical analysis techniques. The resulting quality of the total value reached 75.4%. the interaction dimension got an average effect of 75.7%, and the overall dimension got an average value of 75.5%. These four dimensions fall into the Good category. This can be interpreted that the overall quality of the Spry application in the community is good. The Sigap application for disaster information is of good quality which is presented to disaster response volunteers and the community in general. In addition, valid information, which can be accessed by all people and receiving very fast responses or responses from the Sidoarjo Regency BPBD, is a boost to public confidence that the Sigap application is a good disaster application in Sidoarjo Regency.